2010
DOI: 10.4025/actascianimsci.v32i3.7123
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização dos sistemas de produção de leite bovino no Cariri paraibano

Abstract: Objetivou-se, com o presente estudo, caracterizar os sistemas de produção de leite bovino no Cariri da Paraíba, utilizando análise de componentes principais e de agrupamento por Cluster. Foi selecionada uma amostra de 100 produtores rurais nos municípios de Caturité e Barra de Santana para aplicação de um questionário que foi composto por variáveis quantitativas, subdivididas em cinco conjuntos, totalizando 16 perguntas. Os quatro primeiros componentes principais explicaram 75,56% da variação total. Verificou-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
0
5
0
2
Order By: Relevance
“…Existem vários estudos sobre a caracterização da bovinocultura no Brasil (CARVALHO et al, 2001;ALMEIDA et al, 2006;CARNEIRO et al, 2006;SILVEIRA et al, 2006;MIGUEL et al, 2007;MOURA et al, 2010b;SILVA et al, 2010), no entanto, não há uma padronização na metodologia de avaliação e caracterização dos sistemas produtivos que se torna mais complicado pela elevada quantidade de características que precisam ser analisadas (PEREIRA, 2001).…”
Section: Introductionunclassified
“…Existem vários estudos sobre a caracterização da bovinocultura no Brasil (CARVALHO et al, 2001;ALMEIDA et al, 2006;CARNEIRO et al, 2006;SILVEIRA et al, 2006;MIGUEL et al, 2007;MOURA et al, 2010b;SILVA et al, 2010), no entanto, não há uma padronização na metodologia de avaliação e caracterização dos sistemas produtivos que se torna mais complicado pela elevada quantidade de características que precisam ser analisadas (PEREIRA, 2001).…”
Section: Introductionunclassified
“…Thus, each selected feature should be responsible for a unique type of information and their joint action should be complementary to the general description of the production system of sorghum silage in Cariri. Moura et al (2010) reported a high correlation (0.7740) between the age of producer and time in the livestock industry. A similar result was obtained in this study (0.9451; P<0.01), which justifies the disposal of the age of producer descriptor.…”
Section: Resultsmentioning
confidence: 99%
“…In this analysis, the first three principal components explained 69.46% of the total variation (Table 4), demonstrating that the technique of PCA was sufficient to identify features responsible for defining the groups or production systems. This approach decreases the level of work involved in the characterization of multiple variables, and concurrently improves the accuracy of the analysis as well as makes the data less complex to analyze and interpret (Moura et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diverse studies were conducted on the characterization of cattle breeding in Brazil (Miguel et al, 2007;Moura et al, 2010;Silva et al, 2010), however, without a standardization in the methodology of characterization of the productive systems, where the characteristics analyzed may be broader or narrower, depending on the purpose of the research.…”
Section: Introductionmentioning
confidence: 99%